ONTOLOGI IBLIS DALAM AL-QUR’AN - Nurul Hakim (IAIN Ponorogo, 2017)
Abstract: The man carrying out his devotion to Allah SWT always harassed by demons. Devil is the enemy of Allah SWT. Indeed, the existence of Devil as the enemy of Allah SWT as well as humans. But who is the real devil? Do they belong to certain creature which are different from human beings, jinn, angels, animals and others?. Then, what is exactly interpretation of the devil in human life? This issue is very rarely discussed. The writer concludes that